Knowledge-based open Internet of Things service provisioning architecture on beacon-enabled Web of Objects - Muhammad Golam Kibria; Ilyoung Chong (International Journal of Distributed Sensor Networks)
Web of Objects uses a semantic ontology to create and provide knowledge-based Internet of Things services in terms of virtual objects and composite virtual objects. The objects are created through virtualization with the use of semantic ontology to form the virtual objects, where multiple virtual objects are combined to form the composite virtual objects to offer the services. Beacon-enabled Web of Objects is the extension of the existing web that allows the beacon to broadcast the uniform resource identifier of the real-world object to the nearer mobile devices. Based on the user selection and request, the service is handled and offered by the Web of Objects platform; thus, an architecture on the beacon-enabled Web of Objects has been proposed in this article. To offer the knowledge-based services, a knowledge creation model has been presented. To realize the knowledge-based service features on the proposed architecture, a use case scenario has been presented and a conceptual semantic ontology model has been designed. Finally, to assess the features, a prototype has been implemented and demonstrated on the use case scenario.